Experience with sonogram-guided hydrostatic reduction of intussusception children in South-West Nigeria (2013)
"Background Intussusception is a common cause of intestinal obstruction in young children. The diagnosis and treatment of intussusception has evolved over the years with ultrasound being the first choice imaging technique and a major player in the non-operative reduction of intussusception owing to its advantage of reduced morbidity and non-exposure to ionizing radiation when compared to other modalities of treatment.Aim & Objectives: The aim of this study was to evaluate the efficiency of ultrasound guided hydrostatic reduction in the management of intussusception in children and assess the predictors of reducibility.Methods: A prospective study of all infants and children who presented with uncomplicated intussusception was conducted between January, 2005 and September, 2013. The diagnosis of intussusception was made clinically and this was confirmed by an abdominal ultrasonography. Ultrasound guided hydrostatic reduction of intussusception was performed on the selected patients after they were adequately resuscitated. Failed was abandoned in favour of operative reduction in some patients. Data collected included the age of the patient, duration of symptoms and the outcomes of the procedure and these were analyzed. Results: Eighty-four patients with intussusception were treated over this period, 36(42,9%) patients were found suitable for hydrostatic reduction of intussusception. Twenty-four(66.7%) patients presented within 48 hours of onset of symptoms. Twenty-one(58.3%) patients had successful hydrostatic reduction of intussusceptions while 15 (41.7%) patients had failed reduction. The procedure was successful in majority (58%) of the patients age of 1 year and one of the three (33%) patients older than one year. Hydrostatic reduction of intussusceptions was successful in 14 out of 24 patients (58.3%) who presented within 48 hours of onset of symptoms. Conclusion: Hydrostatic reduction of intussusception under ultrasound guidance is an effective and use conservative method of management in carefidly selected children with intussusception. Overall, this modality treatment is cost effective and could readily be used for patients in resource poor environment. It also monitors the reduction process and visualizes the components of the intussusception including the lead points. "